Peran Media Interaktif dalam Memotivasi Belajar Siswa Berkebutuhan Khusus pada Pembelajaran PAI - Syalihan, Meliny; Nosy Restia; Nur Asyifa Ananda; Jasiah (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
This study discusses the role of interactive media in motivating learning for students with special needs in Islamic Religious Education (PAI). This study uses a literature review method by collecting and analyzing literature related to the role of interactive media in motivating learning for students with special needs. The analysis was carried out qualitatively by describing and integrating findings from various sources. Data validity is maintained by selecting credible and up-to-date sources. In the context of inclusive education, students with special needs often face challenges in understanding the material. The use of interactive media, such as videos and technology-based applications, is expected to increase student engagement and motivation to learn. The results of the study showed that interactive media significantly improved conceptual understanding and created an inclusive learning environment. However, a personal approach is needed to overcome differences in student responses.